2021
DOI: 10.1186/s43055-021-00411-6
|View full text |Cite
|
Sign up to set email alerts
|

The additive role of dynamic contrast-enhanced and diffusion-weighted MR imaging in preoperative staging of breast cancer

Abstract: Background In women with diagnosed breast cancer, accurate loco-regional staging and preoperative examination are of utmost importance for optimal patient management decisions. MRI may be warranted for correct preoperative staging as recommended from international guidelines. DWI-MRI can be combined with CE-MRI to assess more functional data. So we aimed to evaluate the performance of CE-MRI and qualitative DWI-MRI in preoperative loco-regional staging of malignant breast lesions as regards the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The present study revealed that CEM was more accurate regarding multiple lesion detection compared to MRI, while Anwar et al (20) reported that the diagnostic accuracy of MRI was higher than that of CEM, and Hashem et al (16) found the accuracy of MRI was 83.78%.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…The present study revealed that CEM was more accurate regarding multiple lesion detection compared to MRI, while Anwar et al (20) reported that the diagnostic accuracy of MRI was higher than that of CEM, and Hashem et al (16) found the accuracy of MRI was 83.78%.…”
Section: Discussionmentioning
confidence: 44%
“…The choice between total mastectomy and breast-conserving surgery depends on multiple factors, including the extent of cancer and its multifocality or multicentricity. Tumour extent overestimation can lead to avoidable mastectomies, while underestimation can lead to re-operations or recurrence (11,16). Accurate breast imaging and identification of additional malignant foci may, in the future, reduce the quantity of postoperative breast radiotherapy after conserving surgery and correspondingly decrease the number of complications in those patients, which will consequently lower treatment costs (12).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they stated that qualitative DWI could be accompanied by ultrasonography to better assess the axillary nodal status. Both combinations enable the preoperative loco-regional staging of malignant breast disease to be effective and precise [ 69 ].…”
Section: Dwi In Treatment Evaluation Of Breast Cancermentioning
confidence: 99%